GoBeli: providing runner platform for personal sand delivery services for urban community - Ahmad Dahlan, Abdul Rahman; Nordzi, Muhammad Aidid Wafi; Muhammad Farhan, Mohd Hatta (IEEE, 2018)
This paper will discuss about a conceptual solution called GoBeli, an application or platform to cater runner services using on-demand runner booking services from available runner or rider for delivery services. personal shoppers and errand runners. A client is an individual or a group requesting for runner services while a runner is those willing to do runner services and delivery services. The product provides personal shopper or rider as an errand runner to purchase items for customer from groceries to clothes and deliver it to customers’ doorstep. This on-demand runner platform provides delivery upon request to any locations. The products intend to serve runner services in an urban community and give chances to rider to generate income, and a solution for customers who demand for runner services like food delivery, personal shopper and errand runners. It also helps businesses increase their productivity by providing advertising space and delivery Business to Customer (B2C) business.